Respuesta :

Answer:

k = 7

Step-by-step explanation:

The given figures are lines f(x) and g(x)

For the line f(x), we have the y-intercept at (0, -3) and slope = (-1 - (-3))/(-3 - 0) = -2/3

Therefore, line f(x) = y - (-3) = -2/3·(x - 0) which gives f(x) = y = -3 - 2·x/3

For the line g(x), the y-intercept is (0, 4), and the slope is (4 - 2)/(0 - 3) = -2/3

The equation of the line g(x) is therefore, g(x) = y - 4 = -2/3·x, which simplifies to the slope and intercept form as g(x) = y = 4 - 2/3·x

Therefore, given that the transformation of f(x) to g(x) is given as g(x) = f(x) + k, we have;

k = g(x) - f(x) = 4 - 2/3·x - (-3 - 2·x/3) = 4 - 2/3·x + 3 + 2·x/3 = 7

∴ k = 7

ACCESS MORE